2020
DOI: 10.1101/2020.08.03.234401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate risk to European fisheries and coastal communities

Abstract: With the majority of the global human population living in coastal regions, identifying the climate risk that ocean-dependent communities and businesses are exposed to is key to prioritising the finite resources available to support adaptation. Here we apply a climate-risk analysis across the European fisheries sector for the first time to identify the most at-risk fleets and sub-national regions. We combine a trait-based approach with ecological niche models to differentiate climate hazards between population… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Projected losses in cold-water habitat under future climate warming may put 30% of current spending at risk by 2080 (US$192 million year −1 ), representing 21% of the total annual fishing economy in the region ( 21 ). These findings are similar to climate projections from other studies in commercial and recreational fisheries ( 13 , 14 , 16 , 18 ). Droughts and associated extreme events (e.g., wildfires and heat waves) will likely exacerbate these impacts for some local economies as fishers avoid poor fishing conditions and management closures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Projected losses in cold-water habitat under future climate warming may put 30% of current spending at risk by 2080 (US$192 million year −1 ), representing 21% of the total annual fishing economy in the region ( 21 ). These findings are similar to climate projections from other studies in commercial and recreational fisheries ( 13 , 14 , 16 , 18 ). Droughts and associated extreme events (e.g., wildfires and heat waves) will likely exacerbate these impacts for some local economies as fishers avoid poor fishing conditions and management closures.…”
Section: Discussionsupporting
confidence: 90%
“…Shifts in species distributions in response to climate change have been documented for a broad range of organisms (11), especially ectothermic species like fishes that are strongly tied to water temperature (12). Such climate-induced range shifts may change the distribution of fishing opportunities across landscapes, requiring fishers to adapt by catching different species or fishing in new locations (13)(14)(15). Globally, extreme climatic events (e.g., droughts, storms, heat waves, and wildfires) are increasing in frequency and severity and may also affect fishing opportunities by affecting fishers' decisions on where and when to fish (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018—with the most recent, complete statistics—these stocks contributed 84% to all fisheries landings in the North East Atlantic, with, as expected (Gullestad et al., 2020), a substantial variation in landed tonnes across stocks (Appendix S1, Table S4). A recent hazard metric analysis, based on the negative impact of exceeding a stock‐specific thermal safety margin, concluded that European fishing fleets operating in the North Sea, English Channel and Celtic and Irish Seas are particularly at high climate risk, that is encountering adverse consequences (Payne et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Climate fluctuations and change (Bindoff et al., 2019; IPCC, 2013, 2021) affect ecosystems by altering regional productivity (Free et al., 2019; Lehodey et al., 2006) and typically displacing species polewards (Poloczanska et al., 2013), though predicted shifts are less and more mixed with the RCP4.5 compared with the RCP8.5 scenario (Morley et al., 2018). Such responses are constrained by stock‐specific habitat availability, ocean circulation patterns and bathymetry (Brander, 2007; Gullestad et al., 2020) and by physiological features like metabolic processes restricted to tolerable thermal windows (Cheung et al., 2013; Payne et al., 2021; Pörtner & Peck, 2010). Therefore, different stocks may respond in many ways to regional climate change.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a framework (Box 2) where scientifically supported transboundary governance will avoid overexploitation, conflicts about newly or historically shared resources, and conservation of vulnerable species. Global research efforts (as in this study) can be further developed to identify vulnerable species, for instance by applying a trait‐based approach (Albouy et al., 2020; Payne et al., 2020). Identifying vulnerable relocating or shifting species and building the capacity for adaptation can both aid responsive and efficient governance of species affected by climate change.…”
Section: Tracking Species Densities Across Management Areasmentioning
confidence: 99%